Quantum particle motion on the surface of a helicoid in the presence of an harmonic oscillator - Marcos C.R. Ribeiro, Jr.; Márcio M. Cunha; Cleverson Filgueiras; Edilberto O. Silva (Physics Open, 2020)
The geometric potential in quantum mechanics has been attracted attention recently, providing a formalism to investigate the influence of curvature in the context of low-dimensional systems. In this paper, we study the consequences of a helicoidal geometry in the Schrödinger equation dealing with an anisotropic mass tensor. In particular, we solve the problem of an harmonic oscillator in this scenario. For some specific conditions, we determine the wavefunction in terms of Confluent Heun Functions and compute the respective energy. The system exhibit several different behaviors, depending on the adjustment on the mass components.